SOCIAL DOMINANCE ORIENTATION, MORAL DISENGAGEMENT, AND MASCULINITY AS PREDICTORS OF STREET HARASSMENT PREVALENCE - Almerino, Jeanne Therese Fin; Licayan, Elle Danielle Tan; Rocamora, Christine Angel Ramas; Trangia, Michelle Plaza; Almerino, Jana Gloria Fin; Almerino, Porferio Manilag (Psychological thought, 2025)
Street harassment targeting women has persisted as an ongoing societal issue. This study examined masculinity, Social Dominance Orientation, and moral disengagement as predictors of street harassment behavior among men. Using convenience sampling, male participants (N = 211) completed questionnaires measuring these variables. Multiple regression analysis was used to assess predictive relationships, and internal consistency was examined. Results demonstrated that masculinity, Social Dominance Orientation, and moral disengagement significantly predicted street harassment frequency, with masculinity emerging as the strongest predictor. The study provides empirical support for understanding psychological factors underlying street harassment perpetration, offering insights for intervention strategies and further research implications discussed within the paper. This study presents a predictive model for street harassment frequency, shedding light on the motivations of male perpetrators and contributing to research on gender and behavior. However, these findings are only a starting point. Greater awareness, further research, and practical solutions are required to fully address and eradicate street harassment.